Oportunidades del sector agrícola colombiano dentro de la Alianza del Pacifico (2020)
The Pacific Alliance is constituted as an open integration in Latin America, which has meant that it poses several challenges and challenges for the future.Within the process of liberalization of goods and the reduction of tariffs, there is the agricultural sector that has had a series of products of special treatment in the country in order to generate a competitive market but that for the rest of products and due to the competitive advantages of Colombia, it can be a framework of opportunities and advantages for this sector. The present work aims to show the level of economic integration that the Pacific Alliance has reached, its characteristics, progress and the opportunities it has generated for the agricultural sector in the country.